Dinamika Pelaksanaan Pembelajaran IPS Berdiferensiasi dalam Kelas Heterogen di MTs Manbaul Hikmah Pondok Pesantren Gedongan - Alwi, Mohamad; Syauqi, Muhammad (IJTIMAIYA: Journal of Social Science and Teaching, 2025)
This study aims to describe the implementation of differentiated learning in social studies at MTs Manbaul Hikmah, a school under the auspices of Gedongan Islamic Boarding School. Differentiated learning attempts to adapt the learning process to the needs, interests, and individual characteristics of students. This approach is important because each student has a different background, potential, and learning style. The study used a descriptive qualitative method with a focus on grade VII. Data were obtained through observation, interviews with social studies teachers, the vice principal for curriculum, and students, and supported by learning documentation. The results showed that teachers were able to adapt differentiated strategies in a heterogeneous classroom context, despite facing limitations of time, resources, and the Islamic boarding school culture that emphasizes uniformity. The novelty of this study lies in the study of the implementation of differentiated learning in the Islamic boarding school environment, contributing to the development of inclusive and contextual learning strategies in Madrasah Tsanawiyah.